Estimating the Cost-Effectiveness of Tumor Treating Fields (TTFields) Therapy with an Immune Checkpoint Inhibitor or Docetaxel in Metastatic Non-Small Cell Lung Cancer - Furnback W; Wu E; Koh CYC; Nino de Rivera Guzman JF; Kruhl C; Kotecha R; Wang BC (ClinicoEconomics and Outcomes Research)
Wesley Furnback,1 Elizabeth Wu,1 Cloe Ying Chee Koh,2 Jorge Fernando Nino de Rivera Guzman,2 Christian Kruhl,3 Rupesh Kotecha,4 Bruce CM Wang3 1Real Chemistry, New York, NY, USA; 2Novocure, Inc, Portsmouth, NH, USA; 3Novocure GmbH, Root, Switzerland; 4Department of Radiation Oncology, Miami Cancer Institute, Baptist Health South Florida, Miami, FL, USACorrespondence: Bruce CM Wang, Novocure GmbH, Neuhofstrasse 21, Baar, 6340, Switzerland, Email bcwang@novocure.comPurpose: Lung cancer remains a leading cause of cancer-related mortality. Tumor Treating Fields (TTFields) therapy extended survival in patients with metastatic non-small cell lung cancer (NSCLC) on or after platinum-based therapy. This study evaluates the cost-effectiveness of TTFields therapy concomitant with immune checkpoint inhibitors (ICIs) or docetaxel.Methods: A model-based health economic evaluation estimated lifetime costs, clinical benefits, and humanistic outcomes of TTFields therapy plus ICI or docetaxel versus ICI or docetaxel alone in metastatic NSCLC. The model used clinical data from the LUNAR study, US healthcare cost data, and quality-adjusted life year (QALY) measures.Results: The addition of TTFields therapy to an ICI or docetaxel resulted in a mean life-year gain of 0.92 and a QALY gain of 0.66, with an incremental cost-effective ratio (ICER) of $89,808 per QALY gained. TTFields therapy plus an ICI had 1.67 additional life years and 1.21 additional QALYs compared to an ICI alone, with an ICER of $58,764 per QALY gained. For TTFields therapy plus docetaxel, the life-year gain was 0.23 and the QALY gain was 0.17, with an ICER of $306,029 per QALY gained. Sensitivity analyses confirmed the robustness of these findings.Conclusion: The addition of TTFields therapy to an ICI or docetaxel in metastatic NSCLC demonstrates comparable cost-effectiveness to other approved treatments. ICERs fall within the accepted range for US cost-effectiveness thresholds, supporting their use in clinical practice. TTFields therapy extended mean lifetime survival, offering a clinically meaningful and economically justifiable option for patients progressing after platinum-based chemotherapy.Plain language summary: Recent clinical data from the LUNAR study has shown that Tumor Treating Fields (TTFields) therapy concomitant with immune checkpoint inhibitors (ICIs) or docetaxel improves survival in patients with metastatic non-small cell lung cancer (NSCLC) on or after platinum-based therapy. TTFields therapy recently received FDA approval for use in this setting. The aim of this study was to assess whether the addition of TTFields therapy was cost-effective compared to using ICIs or docetaxel alone. A model assessing treatment benefit, costs over the patient’s lifetime, and general health and well-being or life satisfaction was generated using clinical data from the LUNAR study and quality-adjusted life year (QALY) measures. QALY is a metric incorporating length of life and quality of life. The study shows that TTFields therapy concomitant with ICIs or docetaxel is cost-effective in comparison with other treatments currently approved for metastatic NSCLC treatment supporting a potential approval for TTFields therapy in this setting.Keywords: lung cancer, chemotherapy, immunotherapy, cost-effectiveness, Tumor Treating Fields